2018
DOI: 10.1136/bmjopen-2018-023496
|View full text |Cite
|
Sign up to set email alerts
|

Plain packaging of waterpipe tobacco? A qualitative analysis exploring waterpipe smokers’ and non-smokers’ responses to enhanced versus existing pictorial health warnings in Egypt

Abstract: ObjectiveDespite the global increase in waterpipe tobacco smoking (WTS) including in Egypt, few studies have assessed the effectiveness of waterpipe tobacco (WT) health warnings. Egypt has used pictorial health warnings (PHWs) on waterpipe tobacco packs (WTPs) and has rotated these every two years since 2008. We explored in this qualitative study how participants perceived existing PHWs on WTPs, assessed how they interpreted novel plain packaging of WT featuring enhanced PHWs, and probed perceptions of how exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 52 publications
(44 reference statements)
1
20
0
Order By: Relevance
“…The content of the existing warnings studied in this research were about smoking in general and not WTS in particular, although they appeared on WTPs. A recent report of the WHO recommended waterpipe-specific product labelling to improve the intended effects of the health warnings [5], as well as more recent quantitative [26,27,32] and qualitative [28,29,30, 31] research on PHWs on WTPs. Warnings with waterpipe-specific text and images may render PHWs on WTPs more believable, especially among participants who do not react affectively to PHWs or are resistant to changing their WTS habits or less concerned about WTS health hazards.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The content of the existing warnings studied in this research were about smoking in general and not WTS in particular, although they appeared on WTPs. A recent report of the WHO recommended waterpipe-specific product labelling to improve the intended effects of the health warnings [5], as well as more recent quantitative [26,27,32] and qualitative [28,29,30, 31] research on PHWs on WTPs. Warnings with waterpipe-specific text and images may render PHWs on WTPs more believable, especially among participants who do not react affectively to PHWs or are resistant to changing their WTS habits or less concerned about WTS health hazards.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, health warning labelling of non-cigarette tobacco products, including waterpipe tobacco, remain understudied. To our knowledge, few published studies have examined the impact of waterpipe tobacco PHWs: two online surveys from Canada and the US—both countries do not require PHWs on waterpipe tobacco packs (WTPs) [26,27], four qualitative studies from the UK, Egypt and the EMR [28, 29, 30, 31] and one survey from Egypt that explored expert and public opinion of the visibility of existing PHWs on WTPs and their best likely position on waterpipes [32]. The first two studies were experimental and tested hypothetical text-only versus PHWs, with limited effect on established waterpipe users.…”
Section: Introductionmentioning
confidence: 99%
“…The decision included the closure of all restaurants and cafes for the same period of time [26]. Water pipe smoking is growing in Egypt [27], and among our participants, about 5% used to smoke water pipes, which may be a source of transmission of COVID-19 through the sharing of mouth pieces and hoses [28]. Accordingly, the decision of the government may help prevent this source of transmission of infection.…”
Section: Attitudes Towards the Preventive Measures Of Covid-19mentioning
confidence: 99%
“…Another study among adolescents and young adults (both users, and susceptible non-users) argued that adolescents and young adults underestimate and discount the long-term risks associated with waterpipe use, and therefore effective messages may be those that focus on the acute/immediate health and cosmetic effects 45 . Another study also showed that warnings featuring more immediate effects such as harmful effects on teeth were the most effective 40 . According to an expert panel of waterpipe scientists, the most important waterpipe-specific health warnings include labels on oral and heart disease, harmful effects on new-born children and the amount of smoke inhaled from WP compared to cigarettes 46 .…”
Section: Packaging Warning and Labellingmentioning
confidence: 98%
“…Studies revealed that packs are considered less attractive and health warnings are more impactful as health warnings increase in size and packaging becomes less branded 39 ; larger warnings in plain packaging instead of colorful packages are consider more effective in preventing initiation and stimulating smoking cessation 40 .…”
Section: Packaging Warning and Labellingmentioning
confidence: 99%